Water Quality Assessment of Roof-collected Rainwater in Miri, Malaysia - Joel Joseph Hughes Frichot; Rubiyatno; Gaurav Talukdar (Tropical Aquatic and Soil Pollution, 2021)
Rainwater harvesting systems are becoming more acceptable as an alternative method to harvest water sources for both potable and non-potable uses. While the method has proven to be very simplistic and cost-effective, the collected rainwater source remains untreated and can pose serious health concerns if not used properly. This study focused on the physicochemical and heavy metal parameters of roof-collected rainwater in Miri, Sarawak. Individual sites were chosen throughout Miri, Sarawak for representative samples. Atomic Absorption Spectroscopy was used for the analysis of heavy metal concentrations. Heavy metal analysis included manganese, zinc, iron, copper, and cadmium. pH, temperature, turbidity, dissolved oxygen (DO), total suspended solids (TSS), total dissolved solids (TDS), nitrate, and fluoride were among the physicochemical parameters examined. Seasonal comparison indicated the majority of the higher concentration levels occurred during the wet season. The overall mean concentration for the physicochemical parameters indicated CLASS I usage, with the exception of BOD5, which was CLASS III usage. The overall mean concentration for metals analyzed indicated a CLASS I usage threshold with the exception of copper, which had concentrations well above the 0.02mg/L threshold for all sites. Thus, copper was considered one of the major contaminants for this study. Moreover, the types of storage tanks also showcased key findings. Open top storage tanks are more vulnerable to contamination than closed storage tanks. Metal storage tanks offer higher rainwater temperatures in comparison to other types of storage tanks.